Early Childhood Caries: Prevalence, Risk Factors, and Prevention - Anil, Sukumaran; Anand, Pradeep S. (Frontiers in Pediatrics, 2017)
“Early childhood caries (ECC) is major oral health problem, mainly in socially disadvantaged populations. ECC affect infants and preschool children worldwide. The prevalence of ECC differs according to the group examined, and a prevalence of up to 85% has been reported for disadvantaged groups”. “Early childhood caries (ECC) is the presence of one or more decayed, missing, or filled primary teeth in children aged 71 months (5 years) or younger. It begins with white-spot lesions in the upper primary incisors along the margin of the gingiva. If the disease continues, caries can progress, leading to complete destruction of the crown.” The main risk factors in the development of ECC can be categorized as microbiological, dietary and environmental risk factors. Even though it is largely a preventable condition, ECC remains one of the most common childhood diseases. The major contributing factors for the for the high prevalence of ECC are improper feeding practices, familial socioeconomic background, lack of parental education and lack of access to dental care. Oral health plays an important role in children to maintain the oral functions and are required for eating, speech development, and a positive self-image. The review will focus on the prevalence, risk factors and preventive strategies and the management of early childhood caries.